Populations of Aspergillus flavus in field and pod-zone soil in groundnut fields - NAHDI, SALEHA (Indian Phytopathology, 2002)
Populations of A. flavus were estimated for field soil and pod-zone soil during the rainy season from crops of groundnuts (cv. TMV 2) grown in 5 fields in 1988 and 7 fields in 1989 at the ICRISAT Centre, Yemen. Populations were higher in the pod-zone than in the field soil and increased with maturation of the crop. Populations were higher in rainfed fields than in irrigated fields and also higher in fields where groundnuts had been grown the previous year (compared with those which were previously left fallow).